Les disfluences dans le discours radiophonique : signification (s) et fonction (s) communicative (s) - Hamza Kernou (Multilinguales)
This work aims to study verbal disfluences, language tics and disfluencing repetition, in "the antenna is yours", an interactive radio program from Algiers-Chaîne III. This is to demonstrate that verbal disfluencies are not always free, but can have a meaning, a communicative function and play a role in communication and interaction.